Comparison between the European SCORE and the updated SCORE2 for cardiovascular outcomes. (3rd October 2022) - Temtem, M; Mendonca, M I; Serrao, M; Santos, M; Sa, D; Soares, C; Sousa, A C; Rodrigues, M; Freitas, S; Henriques, E; Borges, S; Ornelas, I; et al.
Abstract: Introduction: The European Systematic Coronary Risk Evaluation (SCORE) has predicted a 10-year risk of CVD since 1986. It included only fatal CVD outcomes, underestimating the total CVD burden, especially for younger people. To counteract this issue, a new score was created (SCORE2) to estimate 10-year fatal and non-fatal CVD risk in Europeans without previous CVD or diabetes aged 40–69 years. Purpose: Establish a comparison between SCORE and SCORE2 in terms of CV outcomes in a moderate-risk population. Methods: A population of 1, 178 individuals without CVD (mean age 53.3±6.9 years; 73.9 male) was stratified into three risk categories for SCORE and SCORE2: low, moderate and high-risk. Using t-test and Chi-square, we compared the two scores in terms of means and risk categories. Kaplan-Meier estimator evaluated MACE occurrence for each category of the two scores during an extended follow-up (mean of 5.2±3.4 years). MACE discriminative capacity of SCORE and SCORE2 was evaluated through C-index methodology. Results: The means of the two scores were significantly different (p<0.0001): 2.1±2.4 for SCORE and 6.0±3.3 for SCORE2. 51% of the individuals with high-risk SCORE2 presented the lowest value of SCORE (0–5%). Kaplan-Meier curves showed that the highest category had a worst survival for each score. SCORE2 showed a better discriminative capacity for MACE (C-index 0.678) relatively to SCORE (C-index 0.591), with statistical significance (p<0.0001). Conclusion: SCORE2 enhanced the identification of individuals at higher risk of developing CVD and better discriminated MACE occurrence relatively to SCORE. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): SESARAM EPERAM